1998
DOI: 10.1038/sj.bmt.1701275
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in patients undergoing bone marrow transplantation for myeloid malignancies

Abstract: Summary:Bone mineral density (BMD) was measured in 23 patients who had undergone bone marrow transplantation (BMT) at the University of Minnesota for myeloid leukemia. The median age at BMT was 22 years (range 3-53) and the median age at assessment of BMD was 27 years (range 4-56). Total body BMD was measured a median of 2 years (range 1-10) after BMT using Dual Photon X-ray Absorptiometry (DEXA). BMD was measured in g/cm 2 , with results expressed as percent of normal values and as Z (standard deviation) scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 23 publications
5
59
1
Order By: Relevance
“…Males with greater post transplant complications had greater loss of BMD. 24 As also reported by Bhatia et al, 25 we found no such correlation in our pediatric cohort.…”
Section: 425contrasting
confidence: 32%
See 2 more Smart Citations
“…Males with greater post transplant complications had greater loss of BMD. 24 As also reported by Bhatia et al, 25 we found no such correlation in our pediatric cohort.…”
Section: 425contrasting
confidence: 32%
“…Bhatia et al 25 reported that the DXA-determined BMD of 10 pediatric patients aged 3 to18 years, most of whom underwent allogeneic BMT for AML, was significantly decreased (median Z-score of À0.5) and lower than that of 13 adults in the same study (median Z-score of 0.0, P ¼ 0.03). Our study corroborates the finding of BMD deficits in a larger cohort of pediatric alloBMT survivors.…”
Section: 425mentioning
confidence: 90%
See 1 more Smart Citation
“…In one study BMD did not change after intensive therapy but the patients had undergone autologous transplantation after which the risks for osteoporosis are obviously much less than after allogeneic BMT. 13 In the recent cross-sectional study by Bhatia et al 18 BMD was decreased in children but not in adults. This finding disagrees with our results but can possibly be explained by a smaller number of adult patients (n = 13, of whom 11 received allogeneic BMT) and by the fact that this patient material consisted mainly of patients with CML where usually only light chemotherapy has preceded BMT.…”
Section: Discussionmentioning
confidence: 99%
“…6 It has been described after hematopoietic stem cell transplantation (SCT) as well, with the majority of cases reported in alloSCT recipients. [7][8][9][11][12][13][14][15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35] AlloSCT-associated BMD loss is usually described in the first 6-12 months after the transplantation, but varies widely from 40 days 17 to 4-6 years after the transplantation, 30,31,34 and in some instances can persist for 10-12 years. 26,28 Baseline BMD pre-SCT is usually within the normal limits; [15][16][17]24,[27][28][29][30]33 the few exceptions noting high O/O prevalence pre-SCT are probably due to the underlying diseases or intensive chemotherapy prior to the transplantation.…”
Section: Introductionmentioning
confidence: 99%